ESTABLISHING DIALOGUES: CONTRIBUTIONS OF EDUCOMMUNICATION TO THE LANGUAGE TEACHING AND LEARNING PROCESS - Ross, Andréa Duarte; Lindstron, Jacqueline Andreucci (Seven Editora, 2025)
This chapter discusses educommunication as an innovative approach to foreign language teaching, grounded in Vygotsky's socio-interactionist theory and aligned with the National Common Curricular Base (BNCC). The qualitative and applied research resulted in the development of an educational booklet for students and teachers of Languages and Literature, aiming to bridge the gap between theory and pedagogical practice. The proposed material promotes the critical and creative integration of media into the teaching-learning process, valuing student content production, student empowerment, and democratic access to information. The booklet represents a significant initiative to enhance teacher training in the context of digital culture and media literacy.DOI: https://doi.org/10.56238/sevened2025.030-028